A Pilot Digital Intervention Targeting Loneliness in Youth Mental Health - Lim, Michelle H.; Rodebaugh, Thomas L.; Eres, Robert; Long, Katrina M.; Penn, David L.; Gleeson, John F. M. (Frontiers in Psychiatry, 2019)
Background: Loneliness is an emerging issue for young people but yet many interventions to address loneliness in this group focus on providing social opportunities. While these sorts of interventions may appear increase social connections, loneliness is more related to quality rather than quantity of social relationships. Thus, interventions addressing loneliness should focus on maximizing the quality of current relationships. Together with youth consumers both with mental ill health and those without, we developed a digital smartphone application (app) called +Connect. The six-week program delivers positive psychology content designed to improve relationship quality. We tested the acceptability, feasibility, and safety of the program in lonely young people with or without a mental health diagnosis of social anxiety disorder. We used a mixed methods study design to triangulate pilot quantitative and qualitative data in young people with and without social anxiety disorder (SAD). Method: Nine participants with a diagnosis of social anxiety disorder (Mage = 21.00; SD = 1.41) and 11 participants with no mental health conditions (Mage = 20.36; SD = 2.16) completed the +Connect digital intervention. Results: Those with social anxiety disorder reported less acceptable ratings on outcomes. Feasibility ratings, measured by uptake and app completion, met a priori threshold criteria in both groups. Those with social anxiety disorder yielded more attrition, with almost double the attrition rate compared with those without the disorder. There were no safety issues elicited during the pilot study. In terms of outcomes, exploratory analyses indicated that the app itself is likely to be beneficial rather than cause harm. Our qualitative data indicated both groups reported no negative outcomes and noted that positive outcomes were driven by three processes: reflection, learning, and real-life application. Further exploratory data on usability indicated room for improvement in terms of giving more support for different components of the app (i.e., challenges). Conclusion: The pilot findings of this proof of concept app indicates some promise in terms of a second iterative version of +Connect.